The history of the Jacob Cycle (Genesis 25-35): recent research on the compilation, the redaction, and the reception of the biblical narrative and its historical and cultural contexts - Hensel, Benedikt (Archaeology and bible, 2021)
Cover -- Title -- Preface -- Table of Contents -- Benedikt Hensel - The History of the Jacob Cycle in Recent Research: An Introduction to the Volume -- Konrad Schmid - Shifting Political Theologies in the Literary Development of the Jacob Cycle -- Friederike Neumann - Jacob, Laban, and the Two Daughters: Insights into the Formation of the Jacob-Laban Story (Genesis 29-31) -- Benedikt Hensel - Edom in the Jacob Cycle (Gen *25-35): New Insights on Its Positive Relations with Israel, the Literary-Historical Development of Its Role, and Its Historical Background(s) -- Jakob Wöhrle - Jacob from Israel and Jacob from Judah: Reflections on the Formation and the Historical Backgrounds of the Jacob Story -- Christian Frevel - Jacob as Father of the Twelve Tribes: Literary and Historical Considerations -- Guy Darshan - The Priestly Account of the End of Jacob's Life: The Significance of Text-Critical Evidence -- Aharon Tavger - "And He Called the Name of that Place Bethel" (Gen 28: 19): Historical-Geography and Archaeology of the Sanctuary of Bethel -- List of Contributors -- Index of Sources -- Index of Subjects.